#TITLE_ALTERNATIVE# - PURWITO (NIM : 12211010), SIGIT
The selection of casing setting depth is one of the important task in preparing the well plan. Many aspects, such as lithology, pressure profile prediction, shallow gases, lost circulation and troublesome zones, should be considered in this selection. The selection of casing setting depth by using pressure window curve which is obtained from the pore pressure and formation fracturing pressure curve. Lack of data is the main concern for predicting pore pressure and fracture pressure profile in exploration phase, then give result improper of casing setting depth. The probability of failure due to improper casing setting depth are differential pipe sticking problem and uncontrolled troublesome formation. In purpose to reducing the probability of failure due to casing setting depth selection, proper formation pressure and fracture pressure prediction will be the key to casing setting depth selection. Corrected Eaton’s equations to predict pore pressure and corrected Eaton’s equations to predict fracture pressure has been done with considering constants correction factor in accordance with the character of lithological formations. The constant correction factor are added to Poisson’s stress ratio when determine fracture pressure profile. The value of constants correction are taken from leak-off test (LOT) or formation integrity test (FIT). The constant correction factor are added to D-exponent parameter when determine pore pressure profile. The value of constants correction are taken from mud logging data, and wireline log data. The other parameters must be considered in selection the casing setting depth such as safety margin that consist of surge, swab, and safety factor; differential pipe sticking limit and kick tolerance. The result of this study is the proper casing setting depth selection. Furthermore, this result is applied to evaluate actual design of casing setting depth in well “X”. The result of application shows that the proposed casing setting depth give sufficient protection to the problem formations rather than actual casing setting depth and reduce non-productive time during drilling operation.